PEMBUATAN APLIKASI SISTEM PEMILIHAN PRESIDEN BEM UNIVERSITAS SAHID SURAKARTA MENGGUNAKAN FINGERPRINT - Muhammad NR Hidayatullah; Dahlan Susilo; Sri Huning Anwariningsih (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2021)
The election process for the BEM president at Sahid Surakarta University previously used a website and log in using a username and password. The implementation of the election has several problems, such as multiple voting rights and an unregistered NIM. Therefore it is necessary to increase security by using applications and fingerprints for login. This study aims to build an application for the presidential BEM election system. The use of fingerprints to improve security in elections and avoid fraud during general elections. This research is software development using the waterfall method. The data collection is divided into three, namely observation, interviews, and documentation. In building the system, it uses the Embarcadero Delphi XE8. The database used by PostgreSQL and the fingerprint used by the Live 20R fingerprint. The system was tested using the Five View method. The fingerprint recording test used three different materials. The fingerprint recognition test used eight different finger conditions. The last test was the application delay time in the fingerprint response and the response to opening the menu. This research is the application of the presidential BEM election system for Sahid Surakarta University using fingerprint. The results of the tests carried out give 100% of the application running functionally. Meanwhile, fingerprint testing results show that the fingerprint machine only reads the fingerprints, while the fingerprint photos and the skin on the elbow cannot be read and stored by the machine. Fingerprint recognition testing using a fingerprint machine can read fingerprints in all conditions (wet fingers, oily fingers, inked fingers, pen crossed fingers, and sanitized fingers). However, fingerprints cannot read if the finger pattern is closed or blocked; namely, fingers closed one hand, fingers dusty, and fingers tied with thread. The time delay test produces an average time for fingerprint reading of 1.05 seconds, while the average time needed for menu opening is 0.25 seconds.